Relationship between pain intensity, pain catastrophizing, and self-efficacy in patients with frozen shoulder: a cross-sectional study - Junya Hirata (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Pain catastrophizing and self-efficacy are useful for predicting pain; these are associated with pain intensity and facilitate evaluation of psychological factors. However, it remains unclear whether the effects are direct or indirect in patients with frozen shoulder; the impact on each variable has also not been clarified. Thus, this study aimed to examine the structural relationship between pain catastrophizing, self-efficacy, and pain intensity in patients with frozen shoulder. Methods Participants who were diagnosed with frozen shoulder between January 2016 and March 2017 were recruited from a single orthopedic clinic. Patients aged 18 years or older, who had been symptomatic for < 1 year and reported localized pain in one shoulder, experienced night pain, and had restricted active and passive shoulder motions were included. Pain intensity (Numerical Rating Scale (NRS)), pain catastrophizing (Pain Catastrophizing Scale (PCS)), and self-efficacy (Pain Self-Efficacy Questionnaire (PSEQ)) were measured at the first examination, and the relationship was examined using the Bayesian estimation method. The model was modified repeatedly based on the posterior prediction p value, deviance information criterion (DIC), and Bayesian information criterion (BIC); the model with the highest explanatory power was adopted as the final model. Results Ninety-three patients diagnosed with frozen shoulder were included in this study. On path analysis, the model in which pain intensity affected psychological factors had the most explanation. The convergence index potential scale reduction was below 1.1, and the convergence of the estimate was confirmed. The posterior prediction p value was 0.25, DIC = 1328.705, and BIC = 1356.872; the validity of the fit of the model was confirmed. The path coefficients from the NRS to the PSEQ, from the NRS to the PCS, and from the PSEQ to the PCS scores were − 0.232 (95% confidence interval (CI), − 0.406 to − 0.033), 0.259 (95% CI, 0.083–0.419), and − 0.504 (95% CI, − 0.646 to − 0.334), respectively; these values were statistically significant (p < 0.05). Conclusion Our results show that pain intensity increases the risk of chronic pain including pain catastrophizing and self-efficacy and that pain catastrophizing increases by decreasing self-efficacy in patients with frozen shoulder.